Covid-19 Requires a Social Medicine Response - Trout, Lucas Jacob; Kleinman, Arthur (Frontiers in Sociology, 2020)
Covid-19 is an inherently social disease, with exposure, illness, care, and outcomes stratified along familiar social, economic, and racial lines. However, interventions from public health and clinical medicine have focused primarily on the scale-up of technical and biomedical solutions that fail to address the social contexts driving its distribution and burden. Fused with a moment of reckoning with racial injustice and economic inequality in the U.S. and across the world, these disparities charge policy leaders to develop, study, and share a response grounded in social medicine. As a yardstick for formulating, evaluating, and implementing health policy and care delivery, social medicine recommends at least three things: integrating health, social, and economic responses; bringing care to the points of greatest need; and focusing on broad equity-driven reforms in the pandemic’s wake. With these tools, Covid-19 presents us with an opportunity to address the inequities that the disease highlights, exploits, and may otherwise entrench.